2014
DOI: 10.1179/1607845414y.0000000161
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in malignancies: Pathogenetic and diagnostic considerations

Abstract: Diagnostic approaches to the anemic cancer patient begin with a detailed clinical history and physical examination. Peripheral blood morphology and reticulocyte count are also helpful. Patients with unexplained anemia are evaluated by standard approaches also used in patients of similar age without malignancy. Serum iron profile and bone marrow examination are often required in difficult cases. This review focuses on major aspects of the pathogenesis of the individual entities. Diagnostic approaches and uncomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 43 publications
5
92
0
3
Order By: Relevance
“…25,26 Low hemoglobin levels contribute to tumor hypoxia which is responsible for enhanced tumor growth; in addition, anemia can promote angiogenesis and genomic mutations in cells. 27 Serta et al 28 observed the level of hemoglobin was lower in patients with CRC compared to a control group. Several studies have demonstrated that preoperative hemoglobin levels were related to the prognosis of tumors, patients with pretreatment hemoglobin 12 g/dL, or less potentially yielding worse outcomes in breast cancer, 29 ovarian cancer, 30 and transitional cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Low hemoglobin levels contribute to tumor hypoxia which is responsible for enhanced tumor growth; in addition, anemia can promote angiogenesis and genomic mutations in cells. 27 Serta et al 28 observed the level of hemoglobin was lower in patients with CRC compared to a control group. Several studies have demonstrated that preoperative hemoglobin levels were related to the prognosis of tumors, patients with pretreatment hemoglobin 12 g/dL, or less potentially yielding worse outcomes in breast cancer, 29 ovarian cancer, 30 and transitional cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is the most common "hematological complication, " found in ∼40-64% of patients with malignant diseases (94) and is mostly due to anemia of chronic disease (ACD) (284). ACD is caused by enhanced formation of pro-inflammatory cytokines, which can on the one hand directly inhibit erythropoiesis and on the other hand restrict the availability of iron for erythropoiesis.…”
Section: Immune Activation Causing Tryptophan Degradation and (Conseqmentioning
confidence: 99%
“…Apart from an activated immune system and enhanced Trp breakdown, patients with malignancies frequently suffer from anemia (94). Anemia is a main contributor to sustained fatigue (95), which is the most frequently reported symptom in cancer patients (96), affecting up to 78% (97).…”
Section: Introductionmentioning
confidence: 99%
“…Bi et al [27] found that patients with high preoperative HGB levels and a high body mass index (BMI) had a good postoperative prognosis after RC, and one study showed that HGB was positively correlated with BMI [28]. Preoperative low hemoglobin levels can lead to tumor hypoxia, which promotes tumor growth by stimulating angiogenesis, acquiring genome mutations, and increasing resistance to apoptosis [13,29] and further leads to increased staging and a poor prognosis. On the other hand, it is speculated that tumor-related inflammation may result in the release of various inflammatory factors, which may affect erythropoietin synthesis and lead to the decrease in HGB [30].…”
Section: Discussionmentioning
confidence: 99%